Studies on Seed Development and Maturation in Kalmegh (Andrographis paniculata (Burm. F.) Wall. Ex Nees) - A VIJAYAKUMAR; M MANIMOHAN (Seed Research, 2026)
Studies were undertaken at HC & RI, TNAU, Coimbatore in Kalmegh (Andrographis paniculata (Burm. F.) Wall. Ex Nees), to trace the seed development and maturation parameters for harvesting quality seeds, at the department of Seed Science and Technology, Tamil Nadu Agricultural University, Coimbatore. The seeds registered maximum dry weight and dry matter accumulation with maximum germination and vigour in the physiological maturity stage, at 30 days after anthesis, which was associated with the change of colour of pods from light green to light brown. Beyond this stage, splitting of pods occur and resulted in shattering of seeds.